SCAR: Smart Cart based on ARM algorithm and RFID technology - Badi, Rajlakshmi; Momin, Bashirahamad (2018 3rd IEEE International Conference on Recent Trends in Electronics, Information & Communication Technology (RTEICT), 2018)
A supermarket is a place where people get all products in one place. Where supermarkets are more advantageous for shopping, there are also few disadvantages that make people leave supermarkets before billing process at checkout counters due to long queues. The most irritating part during the shopping in supermarkets is waiting in the long queues for billing at checkout counters and having lack of product information, which wastes more time at checkout counters. The proposed system SCAR will give the customers a quick shopping experience by facilitating quick billing system attached to cart using RFID technology and a friendly product recommendation on their smartphones using ARM algorithm. Customer will be aware of shopping is under budget or over budget. Product recommendation sent directly to a smartphone will arouse customer's purchasing desire. Also, this system will lessen the billing staff requirement and will increase the sales productivity. The hardware required to implement this system is inexpensive.